Optimization of media composition for α-amylase production in liquid state fermentation of bitter cassava by aspergillus niger - I.Khalaf, Abu Bakir; Alam, Md. Zahangir; Hamzah, Mohd. Salleh (2013)
A number of media components influencing α-amylase production by Aspergillus niger O103A were studied using local bitter variety of cassava (Manihot escuelenta) as the main substrate. The media components (cassava, maltose, glucose, yeast extract, urea, NH4NO3, KH2PO4, CaCl2, MgSO4.7H2O, NaCl, and FeSO4.7H2O) were analyzed using Plackett– Burman design. Optimal concentrations of the components contributing positively to enzyme production were further determined using one factor at a time (OFAT) method. Among different nitrogen and supplementary carbon sources tested, yeast extract 2 (g/l) and maltose 3 (g/L) were most effective for enzyme production. Where the optimized media resulted in higher enzyme titre of 42 U/ml. The results indicated the efficiency of using PB design and (OFAT) methodology for screening and optimization processes.